Demethylating therapy increases cytotoxicity of CD44v6 CAR-T cells against acute myeloid leukemia - Tang, Ling; Kong, Yingjie; Wang, Haobing; Zou, Ping; Sun, Ting; Liu, Ying; Zhang, Juan; Jin, Na; Mao, Hanwen; Zhu, Xiaojian; Wang, Jue; Meng, Fankai; et al. (Frontiers in Immunology, 2023)
Background CD44v6 chimeric antigen receptor T (CD44v6 CAR-T) cells demonstrate strong anti-tumor ability and safety in acute myeloid leukemia (AML). However, the expression of CD44v6 on T cells leads to transient fratricide and exhaustion of CD44v6 CAR-T cells, which affect the application of CD44v6 CAR-T. The exhaustion and function of T cells and CD44v6 expression of AML cells are associated with DNA methylation. Hypomethylating agents (HAMs) decitabine (Dec) and azacitidine (Aza) have been widely used to treat AML. Therefore, there may be synergy between CD44v6 CAR-T cells and HAMs in the treatment of AML. Methods CD44v6 CAR-T cells pretreated with Dec or Aza were co-cultured with CD44v6+ AML cells. Dec or aza pretreated AML cells were co-cultured with CD44v6 CAR-T cells. The cytotoxicity, exhaustion, differentiation and transduction efficiency of CAR-T cells, and CD44v6 expression and apoptosis in AML cells were detected by flow cytometry. The subcutaneous tumor models were used to evaluate the anti-tumor effect of CD44v6 CAR-T cells combined with Dec in vivo. The effects of Dec or Aza on gene expression profile of CD44v6 CAR-T cells were analyzed by RNA-seq. Results Our results revealed that Dec and Aza improved the function of CD44v6 CAR-T cells through increasing the absolute output of CAR+ cells and persistence, promoting activation and memory phenotype of CD44v6 CAR-T cells, and Dec had a more pronounced effect. Dec and Aza promoted the apoptosis of AML cells, particularly with DNA methyltransferase 3A (DNMT3A) mutation. Dec and Aza also enhanced the CD44v6 CAR-T response to AML by upregulating CD44v6 expression of AML cells regardless of FMS-like tyrosine kinase 3 (FLT3) or DNMT3A mutations. The combination of Dec or Aza pretreated CD44v6 CAR-T with pretreated AML cells demonstrated the most potent anti-tumor ability against AML. Conclusion Dec or Aza in combination with CD44v6 CAR-T cells is a promising combination therapy for AML patients.